2008
DOI: 10.3386/w14198
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Women: Does Exposure Reduce Bias?

Abstract: We exploit random assignment of gender quotas across Indian village councils to investigate whether having a female chief councillor affects public opinion towards female leaders.Villagers who have never been required to have a female leader prefer male leaders and perceive hypothetical female leaders as less effective than their male counterparts, when stated performance is identical. Exposure to a female leader does not alter villagers' taste preference for male leaders. However, it weakens stereotypes about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
257
1
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(284 citation statements)
references
References 47 publications
17
257
1
9
Order By: Relevance
“…In line with Chattopadhyay and Duflo (2004a;2004b), Beaman et al (2010) found that female leaders invest more in drinking water facilities and that the overall quantity of public goods was significantly higher in reserved villages, while the quality of public goods was higher, though not significantly so in statistical terms, in reserved villages.…”
Section: Provision Of Public Goodssupporting
confidence: 59%
See 2 more Smart Citations
“…In line with Chattopadhyay and Duflo (2004a;2004b), Beaman et al (2010) found that female leaders invest more in drinking water facilities and that the overall quantity of public goods was significantly higher in reserved villages, while the quality of public goods was higher, though not significantly so in statistical terms, in reserved villages.…”
Section: Provision Of Public Goodssupporting
confidence: 59%
“…Furthermore, the likelihood of corruption declines where women in reserved councils have previous political experience or after a few years of reservation. By contrast, Beaman et al (2010) found that fewer bribes were paid in reserved councils.…”
Section: Targeting Poverty and Corruptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Changes in team composition may in general have consequences for corporate and political outcomes. Moreover, higher female representation in leadership roles may accelerate gender equality both in the short run, by attracting high-ability women to such roles, and in the long run, by exposing society to female leadership and accelerating changes in social norms (see for example Beaman et al, 2009).…”
Section: Group Preferences and Dynamicsmentioning
confidence: 99%
“…Put 21 Conversely, reforms aiming at gender equality can also backfire (Bøhren and Staubo, 2014). 22 In contrast, experimental data addresses the problem of unobservable characteristics (Beaman et al, 2009). differently, in the loan ceiling-free environment, the credit market was segmented between banks tough on women and MFIs friendly to them. In contrast, the loan-ceiling imposed on microcredit made room for market de-segmentation and the existing bias against women entrepreneurs intensified.…”
Section: Resultsmentioning
confidence: 99%